Strategi Guru Pendidikan Agama Islam Dalam Meningkatkan Prestasi Belajar Peserta Didik Berbasis Strategi Discovery Learning - Elsya Frilia Ananda N; Hafifa Hafifa; Riha Datul Aisyah; Nina Novita; Wismanto Wismanto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research is motivated by the importance of teachers' efforts to change teaching methods and create an attractive teaching atmosphere in the classroom so that students can actively participate in learning in a proactive way. Be active, not passive, to achieve the high learning outcomes achieved by students. The purpose of this study was to determine the strategies of Islamic religious education teachers in improving student academic achievement. This research uses qualitative methods based on field research, research data is collected through observation, interviews, documents, analysis, reduction, presentation and verification of data. The results showed that the PAI teacher's strategy to improve PAI learning is to use